Defense strategies selection based on attack-defense evolutionary game model - Jian-ming HUANG; Heng-wei ZHANG; Jin-dong WANG; Shi-rui HUANG (Tongxin xuebao)
Due to that the current network security researches based on game theory mostly use the completely rationality assumption,which is not consistent with the facts.Under the bounded rationality constraint of network attack-defense,attack-defense evolutionary game model and a method to solve evolutionary stable equilibrium based on the non-cooperative evolutionary game theory was proposed.The optimal defense strategy selection algorithm was designed based on the analysis of the evolutionary stable strategy.The effectiveness of the model and method proposed is verified by simulation results,through which some evolution conclusions of offensive behavior on the premise of limited rationality were drawn.